Portuguese Fertility: Southern or Eastern Behaviour ? - Mendes, Maria Filomena (2014)
Portugal is among the group of European countries that is still not recovering in the cohort fertility level, and at the same time was also the only Southern European country, which remained in the minimum value of 1.3, for the period total fertility rate, in the year of 2009. If we establish a comparison between fertility levels in 2000-2005 and 2006-2010, in the European context Portugal is the only country presenting a negative evolution of period fertility. The main objective of this work is to contextualize the Portuguese fertility and to understand if period fertility behaviour/context are similar to South and Eastern European Countries. On the other hand, understand if the economic, social and cultural contexts have bigger impact in South and East Europe.